Lectures in synergetics - Sugakov, Volodymyr I. (World Scientific, 1998)
This book introduces the reader to the exciting world of the nonlinear phenomena that are studied in synergetics. The book comprises treatises on mathematical methods for the study of nonequilibrium processes and presents versatile phenomena studied in synergetics: multistability, self-oscillation, spatial stratification, autowaves, kinetic phase transitions and chaos. Examples of self-organization in physics, chemistry, biology covered in this volume include laser generation, optical bistability, self-oscillations in semiconductors and chemical reactions, spatial stratification in hydrodynamics and in crystals, auto-waves in semiconductors and nerve fibers and many other phenomena. The majority of the phenomena considered occur in physics but the book is also useful for chemists and biologists.